2001
DOI: 10.2105/ajph.91.10.1686
|View full text |Cite
|
Sign up to set email alerts
|

A Motivational Interviewing Intervention to Increase Fruit and Vegetable Intake Through Black Churches: Results of the Eat for Life Trial

Abstract: Motivational interviewing appears to be a promising strategy for modifying dietary behavior, and Black churches are an excellent setting to implement and evaluate health promotion programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
328
4
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(348 citation statements)
references
References 28 publications
11
328
4
5
Order By: Relevance
“…[62][63][64] The social context and support of religious communities and leaders also is very important to many parents. Although religious organizations are recognized globally as potential partners for promoting social change and justice 65,66 as well as family and community health in urban and high-risk populations, (e.g., 67,68) targeted efforts are needed to engage religious leaders around the issue of parenting education and child discipline specifically. Finally, universal-or population-based efforts, such as public education campaigns, have been utilized successfully in public health efforts regarding issues such as alcohol policy, 69 tobacco use, 70 and getting help for abused children.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] The social context and support of religious communities and leaders also is very important to many parents. Although religious organizations are recognized globally as potential partners for promoting social change and justice 65,66 as well as family and community health in urban and high-risk populations, (e.g., 67,68) targeted efforts are needed to engage religious leaders around the issue of parenting education and child discipline specifically. Finally, universal-or population-based efforts, such as public education campaigns, have been utilized successfully in public health efforts regarding issues such as alcohol policy, 69 tobacco use, 70 and getting help for abused children.…”
Section: Discussionmentioning
confidence: 99%
“…34 MI has been shown to improve patients' general health status or well-being, promote physical activity, help develop healthier nutritional habits, and manage chronic conditions such as mental illness, hypertension, hypercholesterolemia, obesity, and diabetes. [37][38][39][40][41] Randomized controlled trials have shown that brief MI training for clinicians is effective for improving patient medication adherence, especially if there is follow-up contact after an initial training, 42,43 and even at low doses (i.e., two or three sessions). MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…Whereas only a handful of researchers have attempted to integrate MI into BWL treatment, other researchers (Bowen et al, 2002;Resnicow et al, 2001Resnicow et al, , 2004Resnicow et al, , 2005 have reported positive findings from trials using MI strategies as an adjunct to large-scale prevention programs aimed at improving dietary habits. Resnicow and colleagues (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005, for example, have incorporated MI-informed phone calls into prevention programs aimed at promoting fruit and vegetable intake (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005 for large groups of African-American churchgoers.…”
Section: Motivational Interviewing In Behavioral Weight Loss Treatmentmentioning
confidence: 99%
“…Resnicow and colleagues (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005, for example, have incorporated MI-informed phone calls into prevention programs aimed at promoting fruit and vegetable intake (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005 for large groups of African-American churchgoers. Results from studies of these programs indicated that groups receiving MI-informed phone calls reported significantly greater intake of fruits and vegetables at 6 months (Resnicow et al, 2004) and 1 year (Resnicow et al, 2001(Resnicow et al, , 2005 relative to those in a control intervention (Resnicow et al, 2001(Resnicow et al, , 2004(Resnicow et al, , 2005 and those receiving the same self-help materials but no MI phone calls (Resnicow et al, 2001(Resnicow et al, , 2005.…”
Section: Motivational Interviewing In Behavioral Weight Loss Treatmentmentioning
confidence: 99%